Apoptosis in radiation therapy: a double-edged sword - Balcer-Kubiczek, E.K. (Experimental Oncology, 2012)
Radiation therapy achieves its therapeutic effects by inducing apoptosis and non-apoptotic cell death. The aim of this focused review is to highlight the aspects of the cell death pathways most relevant to conventional fractionated radiation therapy. I review reports on how our current understanding of the molecular mechanisms of cell death may enable us to revise the four radiobiological principles (reoxygenation, repair of sublethal damage, redistribution of cells in the cell cycle, and repopulation of surviving cells) for radiation treatment with fractionated dose delivery. Apoptosis and non-apoptotic forms of cell death are not represented in the linear quadratic model, which is clinically used to calculate the effects of different total doses, dose per fraction and fraction number on reproductive cell death, a mode of cell death associated with lethal chromosome aberrations. Examples are provided to justify or not a reassessment of the role of apoptosis and non-apoptotic cell death in radiosensitivity, tumor cell proliferation and tumor microenvironment. As our understanding of apoptosis developed at the molecular level, so did our understanding of other forms of cell death, particularly autophagy and to a lesser extent, senescence. The linear quadratic model remains a guide for the treatment planner. The therapeutic clinical roles of apoptosis and non-apoptotic forms of cell death remain to be defined. Their relative importance will probably lie in tumor developmental history related to its type, size and stage. Radiobiological research should focus on the quantitative effects of dose and fractionation on the radiation induction of apoptotic and non-apoptotic types of cell death and the interplay among cell death pathways. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.